2021
DOI: 10.1002/aur.2579
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity within an anxiety network and associations with anxiety symptom severity in middle‐aged adults with and without autism

Abstract: Anxiety is highly prevalent in autism spectrum disorders (ASDs). However, few functional magnetic resonance imaging (fMRI) studies of ASDs have focused on anxiety (and fewer still on anxiety in middle-aged adults). Thus, relationships between atypical connectivity and anxiety in this population are poorly understood. The current study contrasted functional connectivity within anxiety network regions across adults (40-64 years) with and without autism, and tested for group by functional connectivity interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Offspring's vulnerability to anxiety and depression-like behavior may be attributed to changes in the structure of the brain. Both preclinical and clinical investigations support the notion that abnormal structure and function in several brain regions, including the amygdala, periaqueductal gray, dorsomedial prefrontal cortex, bed nucleus of the stria terminalis, paraventricular nucleus of the hypothalamus, and the locus ceruleus, potentially play a role in the development of anxiety and depressive disorders ( Cross et al, 2016 ; Garcia, 2017 ; Donnici et al, 2021 ; Tung et al, 2021 ); however, the cause of such brain volume alterations in subjects diagnosed with anxiety and depression-like behavior has not been completely identified. A recent study found that fetal programming through exposure to a high-energy diet (HED) led to reduced volume in the nucleus accumbens, hippocampus, and prefrontal cortex of rats displaying depression-like behavior ( Trujillo-Villarreal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Offspring's vulnerability to anxiety and depression-like behavior may be attributed to changes in the structure of the brain. Both preclinical and clinical investigations support the notion that abnormal structure and function in several brain regions, including the amygdala, periaqueductal gray, dorsomedial prefrontal cortex, bed nucleus of the stria terminalis, paraventricular nucleus of the hypothalamus, and the locus ceruleus, potentially play a role in the development of anxiety and depressive disorders ( Cross et al, 2016 ; Garcia, 2017 ; Donnici et al, 2021 ; Tung et al, 2021 ); however, the cause of such brain volume alterations in subjects diagnosed with anxiety and depression-like behavior has not been completely identified. A recent study found that fetal programming through exposure to a high-energy diet (HED) led to reduced volume in the nucleus accumbens, hippocampus, and prefrontal cortex of rats displaying depression-like behavior ( Trujillo-Villarreal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 89%
“…Leslie, Donnici et al, 2021;Garcia, 2017;Tung et al, 2021), however, the cause of such brain volume alterations in subjects diagnosed with anxiety and depression-like behavior has not been completely identified. A recent study found that fetal programming through exposure to a high-energy diet (HED) led to reduced volume in the nucleus accumbens, hippocampus, and prefrontal cortex of rats displaying depression-like behavior (Trujillo-Villarreal et al, 2021).…”
Section: Significancementioning
confidence: 99%